Influence Of Quality Of Work Life On Company And Union Commitment - Fields, Mitchell W.; Thacker, James W. (Academy of Management Journal, 1992)
This study examined changes in union and organizational commitment after the implementation of a joint union-management quality-of-work-life (QWL) program. The results indicated that company commitment increased only when participants perceived the QWL effort as successful, but union commitment increased irrespective of the perception of QWL success.